Analisis miskonsepsi peserta didik dalam memahami materi gerak lurus dan gerak parabola pada kelas X SMAN 1 Padang - Aifah Fauziah; Yenni Darvina (Universitas Negeri Padang, 2019)
The purpose of research analyzes misconceptions of students in understanding the material stairght motion and parabolic motion in class X SMAN 1 Padang. This type of research was descriptive with a quantitative approach. The population this research was all students class X SMAN 1 Padang who were enrolled in the 2018/2019 school year. The sampling in this research taken with purposive sampling technique. The sample in this research consisted of five classes. The research instrument was a multipe choice FCI test question with open reasons accompanied by CRI. The result of anlyziz data gotten that avrage of misconceptions was 67,5%, unknowing was 22,86%, knowing was 8,42%, knowing but not sure was 1,29%. The froms of misconception experienced by students are: 1) heavy bals faster than light balls, 2) the greater the gravitational force if it approaches the ground or the surface of the earth, 3) the acceleration of the beam b is greater than the beam a because when beam a was on the five line beam B was on seven line. The causes of misconceptions are associative thinking, humanistic thinking, wrong intuisi, incomplete/ wrong reasoning, cognitive development, students abilities, and student experience.